Study the Effect of annealing temperature on the Structure of a-Se and Electrical Properties of a-Se/c-Si Heterojunction - Adem, Kadhim A. (Iraqi Journal of Physics, 2009)
In this work Study effect of annealing temperature on the Structureof a-Se and electrical properties of a-Se/c-Si hetrojunction have beenstudied.The hetrojunction fabricated by deposition of a-Se film on c-Si using thermal evaporation.Electrical properties of a-Se/ c-Si heterojunction include I-Vcharacteristics, in dark at different annealing temperature and C-Vcharacteristics are considered in the present work.C-V characteristics suggested that the fabricated diode wasabrupt type, built in potential determined by extrapolation from1/C2-V curve. The built - in potential (Vbi) for the Se/ Si Systemwas found to be increase from 1.21 to 1.62eV with increasing ofannealing temperature